The Effect of Entrepreneurship Mentoring on Increasing Income at Laznas IZI North Sumatra - Muhammad Rizky Ramadhan; Maya Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research is entitled "The Effect of Entrepreneurial Assistance on Increasing Income at LAZNAS IZI North Sumatra". The purpose of this study is to find out and analyze the extent to which the entrepreneurial assistance provided by LAZNAS IZI North Sumatra has an effect on increasing the mustahik income of productive zakat program recipients. The approach used in this study is a quantitative approach with a type of causal associative research. The research population amounted to 60 mustahik recipients of the entrepreneurship assistance program, and the entire population was used as a sample with saturated sampling techniques. Data were collected through a closed-ended questionnaire and analyzed using simple linear regression with the help of the SPSS program version 26.0. This study fills the gap that empirical studies on the effectiveness of the quality of entrepreneurial assistance in productive zakat programs in Indonesia are still limited, especially in the context of measuring the direct economic impact on mustahik. The findings of this study also contribute to the Islamic social finance literature by strengthening the evidence that mentoring is an important instrument in the modern zakat empowerment model. The results of the study show that entrepreneurial assistance has a positive and significant effect on increasing mustahik income. The value of the regression coefficient is 0.587, and the significance level is 0.000 (< 0.05) indicating that any increase in entrepreneurial assistance will increase mustahik income significantly. A determination coefficient value (R²) of 0.466 indicates that 46.6% of the variation in income increase is explained by the entrepreneurial assistance variable, while the remaining 53.4% is influenced by other factors outside the research model. These findings strengthen the view that a planned and sustainable mentoring program is able to form economic independence and improve the welfare of productive zakat beneficiaries.